Development of skeletal muscle atrophy and intermuscular adipose tissue in patients with early breast cancer treated with chemotherapy - Mallard, Joris; Hucteau, Elyse; Bender, Laura; Charlot, Anouk; Debrut, Léa; Pflumio, Carole; Trensz, Philippe; Schott, Roland; Favret, Fabrice; Pivot, Xavier; Hureau, Thomas J; Pagano, Allan F (American Journal of Physiology: Cell Physiology, 2022)
Chemotherapy is a common therapy to treat patients with breast cancer but also leads to skeletal muscle deconditioning. Skeletal muscle deconditioning is multifactorial and intermuscular adipose tissue (IMAT) accumulation is closely linked to muscle dysfunction. To date, there is no clinical study available investigating IMAT development through a longitudinal protocol and the underlying mechanisms remain unknown. Our study was dedicated to investigating IMAT content in patients with early breast cancer who were treated with chemotherapy and exploring the subsequent cellular mechanisms involved in its development. We included 13 women undergoing chemotherapy. Muscle biopsies and ultrasonography assessment were performed before and after chemotherapy completion. Histological and Western blotting analyses were conducted. We found a substantial increase in protein levels of three mature adipocyte markers (perilipin, +901%; adiponectin, +135%; FABP4, +321%; < 0.05). These results were supported by an increase in oil red O-positive staining (+358%; < 0.05). A substantial increase in PDGFRα protein levels was observed (+476%; < 0.05) highlighting an increase in fibro-adipogenic progenitors (FAPs) content. The cross-sectional area of the vastus lateralis muscle fibers substantially decreased (-21%; < 0.01), and muscle architecture was altered, as shown by a decrease in fascicle length (-15%; < 0.05) and a decreasing trend in muscle thickness (-8%; = 0.08). We demonstrated both IMAT development and muscle atrophy in patients with breast cancer who were treated with chemotherapy. FAPs, critical stem cells inducing both IMAT development and skeletal muscle atrophy, also increased, suggesting that FAPs likely play a critical role in the skeletal muscle deconditioning observed in patients with breast cancer who were treated with chemotherapy.